Improving the lifetime of wireless sensor networks based on routing power factor - Alkalbani, Abdullah Said; Mantoro , Teddy; Md Tap, Abu Osman (2012)
In this paper the power efficiency of Wireless Sensor Network (WSN) Power is studied. Power consumption is the main challenge during the routing of the data. The main objective of this study is to address tht afe three routing parameters that affect the network life time such as the initial power of the nodes, the residual power in the nodes and the routing period.